THE HUNGER GAMES: KATNISS EVERDEEN’S EFFORT TO GAIN AMERICAN PRAGMATISM GOALS IN TERMS OF AMERICAN VALUES - Naasa Riandji, Ika Fitri (Jurnal Ilmiah Mahasiswa FIB, 2013)
As one of a popular American novel which was published recently, The Hunger Games composed by Suzanne Collins, provides a significant description about the manifestation of American values portrayed by the main character, KatnissEverdeen.Katniss’ efforts in the novel are in line with the principle of American Pragmatism, which later on can be analyzed by its relation with the idea of American values, the grounding idea of the framing of this great American philosophy. By applying a sociological approach, this study discover the existence of the two roots of American culture known as American values and American Pragmatism, are still preserved. Katniss successfully manifests the goals of American Pragmatism that certainly taken from American values’ idea through her struggle told in the novel. This result leads to the comprehension of how American values influence American’s mind in fulfilling their goals or achievements. Keywords: American Values, American Pragmatism, Manifestation of Effort, The Hunger Games.